(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article provides information on interactive methods that can be used to teach mathematics in primary classes. Interactive methods are aimed at stimulating educational and cognitive motivation, development of independence and activity, education of analytical and critical thinking, formation of communication skills, self-development of students. With the use of interactive teaching methods in mathematics lessons, the level of motivation to learn by subject increases, and the quality of knowledge among students in all training profiles is significantly improved.